Scalable Governance Frameworks for Enterprise Architecture Supporting Oracle Cloud DBAs Serverless Data Pipelines and Proactive API Threat Mitigation (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
Scalable governance frameworks are essential for modern enterprise architectures that support Oracle Cloud DBAs, serverless data pipelines, and proactive API threat mitigation. By combining cloud-native principles, role-based access control, automated policy enforcement, and continuous monitoring, organizations can ensure secure, compliant, and resilient operations across complex IT ecosystems. Serverless data pipelines enable efficient, event-driven data processing and transformation, while integrated analytics provide visibility into performance, compliance, and operational risks. Proactive API threat mitigation, including automated anomaly detection, rate limiting, and security orchestration, protects sensitive enterprise data and maintains service continuity. The framework emphasizes standardization, automation, and auditability, enabling IT teams to scale governance practices without hindering innovation. Together, these strategies provide a robust foundation for secure, adaptive, and scalable enterprise systems in dynamic cloud environments.
Keywords: Enterprise architecture; scalable governance frameworks; Oracle Cloud DBAs; serverless data pipelines; API threat mitigation; cloud-native systems; policy automation; role-based access control; proactive security; event-driven architecture; real-time monitoring; compliance; operational resilience; data security; auditability